Anorexia nervosa and necrotizing colitis: case report and review of the literature. Issue 823 (May 1994) - Sakka, S.; Hurst, P.; Khawaja, H.
Abstract : A 20 year old woman with anorexia nervosa and severe weight loss developed extensive necrotizing colitis after being admitted to hospital for stabilization of her weight. Necrotizing colitis with anorexia nervosa has been reported previously. We report a second case. We believe necrotizing colitis is a true complication of anorexia nervosa and should be considered in the differential diagnosis in patients with primary anorexia who develop an acute abdomen.